2018
DOI: 10.1242/dev.158527
|View full text |Cite
|
Sign up to set email alerts
|

Wnt6 maintains anterior escort cells as an integral component of the germline stem cell niche

Abstract: Stem cells reside in a niche, a local environment whose cellular and molecular complexity is still being elucidated. In Drosophila ovaries, germline stem cells depend on cap cells for self-renewing signals and physical attachment. Germline stem cells also contact the anterior escort cells, and here we report that anterior escort cells are absolutely required for germline stem cell maintenance. When escort cells die from impaired Wnt signaling or hid expression, the loss of anterior escort cells causes loss of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(78 citation statements)
references
References 52 publications
6
72
0
Order By: Relevance
“…Under ideal conditions, newly budded follicles grow and develop into a mature egg over 4-5 days. 9,10 This stereotypical process has been divided into 14 distinct stages, with early stages (Stages 1-6) characterized by rapid follicle growth and follicle cell division; mid-stages (Stages 7-10) characterized by the onset of yolk protein production, elongation of the follicle, growth of the oocyte, and specialization of follicle cells into subtypes such as stretch cells; and late stages (Stages [11][12][13][14] characterized Manuscript (Page 4 of 31) by the death of nurse cells, deposition of the egg shell proteins, and growth of the oocyte to fill the entire volume inside the egg shell ( Fig. 1B).…”
Section: Identification Of Distinct Cell Types In the Ovarymentioning
confidence: 99%
See 1 more Smart Citation
“…Under ideal conditions, newly budded follicles grow and develop into a mature egg over 4-5 days. 9,10 This stereotypical process has been divided into 14 distinct stages, with early stages (Stages 1-6) characterized by rapid follicle growth and follicle cell division; mid-stages (Stages 7-10) characterized by the onset of yolk protein production, elongation of the follicle, growth of the oocyte, and specialization of follicle cells into subtypes such as stretch cells; and late stages (Stages [11][12][13][14] characterized Manuscript (Page 4 of 31) by the death of nurse cells, deposition of the egg shell proteins, and growth of the oocyte to fill the entire volume inside the egg shell ( Fig. 1B).…”
Section: Identification Of Distinct Cell Types In the Ovarymentioning
confidence: 99%
“…Recent studies have identified distinct functions and morphologies for some subsets of IGS cells, [31][32][33][34][35] indicating that the population is heterogeneous. In accordance with this, we identified markers specific for Cluster 3.1.0 or 3.1.1 (Fig.…”
Section: Regions 1 and 2a Contain Distinct But Closely-related Populamentioning
confidence: 99%
“…If germ cells at these stages are ablated in adult Drosophila ovaries, ECs turn over (Kai and Spradling, 2003). Wnt signaling from escort cells interacts antagonistically with terminal BMP signaling to establish a gradient in escort cells that is important for ongoing germ cell development (Song and Xie, 2004;Wang et al 2015a;Mottier-Pavie et al 2016;Wang and Page-McCaw, 2018). In addition, disrupting EC gap junctions (Mukai et al 2011) or steroid signaling (Morris and Spradling, 2012) in escort cells arrests germ cell development.…”
Section: An Initial Population Of Escort-like Pregranulosa Cells Medimentioning
confidence: 99%
“…In Drosophila, early germ cells associate with somatic escort cells that express Wnts (Morris and Spradling, 2011;Kirilly et al 2011;Wang et al, 2015a). Disruption of Wnt signaling in escort cells upregulates BMP signaling and interferes with germ cell development and survival (Mottier-Pavie et al 2016;Wang and Page-McCaw, 2018). Escort cells are displaced from germ cells in mature ovaries by migrating follicle cells which then form a granulosa cell-like epithelial monolayer that mediates subsequent follicle development (Margolis and Spradling, 1995;Nystul and Spradling, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Each GSC niche is composed of several types of somatic cells: a Terminal Filament (TF), which is a stack of about 8 flattened cells, approximately 5 Cap Cells (CCs) present at the base of the TF (Gilboa, 2015), one triangularly-shaped transition cell connecting the TF and CCs (Panchal et al, 2017) and posterior to CCs, the anterior Escort Cells (ECs) ( Fig 1A) (Wang and Page-McCaw, 2018). Both CCs and anterior ECs, are in direct contact with GSCs.…”
Section: Introductionmentioning
confidence: 99%